Profundizando en la situación y perspectivas de futuro del aragonés en la enseñanza reglada. Estructura y primeros resultados de un proyecto de investigación en desarrollo - Campos, I.O. (2015)
Although it was introduced in Primary schools two decades ago, very few research has been focused on the situation and prospects of Aragonese language in the educational field. With the aim of providing a general perspective on this, we are implementing a multimetodological research project mainly focused on the lingüístic attitudes of the educational community (teachers, governing bodies, parents and pupils) located in Alto Aragón territory. We also are focusing on the attitudes of teacher training students of University of Zaragoza.